Vortioxetine Can Be Used Safely to Treat Depression After Implantable Cardioverter Defibrillator Implantation for Congenital Long QT Syndrome: A Case Report - Makio Yamauchi; Koji Otsuki; Kouhei Sato; Michiharu Nagahama; Junya Tanabe; Masatoshi Inagaki (Neuropsychopharmacology Reports)
ABSTRACT Background Vortioxetine, an antidepressant, acts on multiple 5‐hydroxytryptamine receptors in addition to inhibiting the 5‐hydroxytryptamine transporter. Currently, data on the effect of vortioxetine on the QT interval are limited. To the best of our knowledge, whether vortioxetine can safely be used for congenital long QT syndrome (LQTS) has not been reported. Case Presentation We here present the case of a 50‐year‐old Japanese woman who was rushed to our hospital because of a sudden cardiopulmonary arrest. Her corrected QT interval was prolonged to 535 ms. After a thorough examination in the cardiology department, she was diagnosed with congenital LQTS and an implantable cardioverter defibrillator (ICD) implanted. Thereafter, she gradually developed severe depression because of stress associated with ICD implantation. Mirtazapine induced daytime somnolence and duloxetine was relatively ineffective, prompting replacement with vortioxetine at 20 mg daily, which relieved her depression. During the treatment period, her corrected QT interval did not exceed 500 ms, beyond which the risk of cardiac events increases. To our knowledge, this is the first report of the safe use of vortioxetine in a patient with depression comorbid with congenital LQTS. Conclusions After ICD implantation, a patient's mental status should be monitored carefully. Our findings suggest that vortioxetine may be a safe treatment option for depression associated with congenital LQTS.